(untitled) (Precision Medicine Communications, 2024)
Prostate adenocarcinoma, in men, is the fifth leading cause of cancer casualties. Prostate cancer (PCa) is slow-growing with relatively low-grade aggressiveness. The prostate gland in the male reproductive system synthesizes and stores semen and seminal fluid. It sits inferior to the bladder, surrounds the superior part of the urethra and anterior to the rectum, and weighs approximately 20g in adult men. The prostate contains numerous small glands that produce 20% of the seminal fluid. In PCa, the cells of these glands undergo a malignant transformation and become cancerous. Single nucleotide polymorphisms (SNPs) are the most common type of gene variation, and many SNPs are associated with PCa risk. SNPs are small mutations in DNA sequences that can alter the structure and function of proteins. They are often inherited from parents and can vary frequently among different populations. SNPs in candidate genes, such as those involved in cell growth and differentiation, have been proven to increase susceptibility to prostate adenocarcinoma. Identifying SNPs linked with PCa risk can potentially upgrade early detection and disease prevention. The research on SNPs in PCa is still in its early stages. However, the findings to date suggest that SNPs have the potential to be valuable tools for the advancement of the diagnosis, prevention, and treatment of this devastating disease. For instance, rs6983267 and rs1447295 at the 8q24 gene in Caucasians and Asians have a strong association with prostate adenocarcinoma. In contrast, rs16901979 in the same gene in African Americans has shown a significant association with prostate malignancy. Meanwhile, in the European population, rs138213197 has a notable association with PCa. In addition to the association with the disease, SNPs may also be involved in treatment failure or toxicities in patients battling prostate carcinoma. For example, in the English population, rs4646487 CYP4B1 and rs2227291 ATP7A are responsible for toxicities in the treatment of prostate gland carcinoma. In this review, we summarize our understanding of how common genetic variations, SNPs, contribute to the development of PCa and how they may be used to screen for and manage the disease. SNPs are linked with a greater risk of aggressive PCa and represent essential biomarkers. However, in addition to confirming the association of these SNPs in larger cohorts, there remains a need to identify additional clinically relevant genetic biomarkers for screening, detection, validation of diagnosis, prevention, and treatment of prostate cancer.